Efficacy and Safety of Bevacizumab in the Treatment of Pterygium: An Updated Meta-Analysis of Randomized Controlled Trials - Yi Sun; Bowen Zhang; Xiuhua Jia; Shiqi Ling; Juan Deng (Journal of Ophthalmology)
Purpose. Studies investigating efficacy and safety of bevacizumab in pterygium have increased and reported controversial results. Thus, we updated this meta-analysis to clarify the issue. Methods. Studies were selected through search of the databases Embase, PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL) from their inception up until June 2017. The pooled risk ratio (RR) and 95% confidence interval (CI) were calculated for recurrence and complication rates by using random effects model. Results. 1045 eyes in 18 randomized controlled trials (RCTs) enrolled. Overall, the pooled estimate showed a statistically significant effect of bevacizumab on the reduction of recurrence (RR 0.74, 95% CI 0.56–0.97, P=0.03). Subgroup analyses presented significant results beneficial to bevacizumab (primary pterygium group, RR 0.53, 95% CI 0.33–0.83, P=0.006; conjunctival autograft group, RR 0.48, 95% CI 0.25–0.91, P=0.02; and follow-up longer than 12 months group, RR 0.36, 95% CI 0.13–0.99, P=0.05). No statistically significant difference was observed in complication rates. Conclusions. Application of bevacizumab showed a statistically significant decrease in recurrence rate following removal of primary pterygia, or in cases with conjunctival autograft, or with follow-up longer than 12 months, while complications were not increased.